LOGISTICS ECONOMICS AS A FACTOR IN RELATIONSHIP MARKETING EFFECTIVENESS - Максютенко, Ірина; Сівашенко, Тетяна (SWorldJournal, 2025)
The article explores the relationship between logistics economics and relationship marketing in the context of modern market competition and instability. Key problem areas are identified, including the rising costs of logistics processes, imbalance betwe